ПРОБЛЕМИ ФОРМУВАННЯ ІНФОРМАЦІЇ ПРО ДЕБІТОРСЬКУ ЗАБОРГОВАНІСТЬ З МЕТОЮ УПРАВЛІННЯ ПІДПРИЄМСТВОМ - Goncharova, N.M. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2008)
Present features of information about forming debtor’s indebtedness, peculiarities of its classification as a precondition for forming a rational system of analytical accounting have been examined. A critical analysis of registers of analytical accounting used in the bookkeeping has been made to reflect debtor’s indebtedness.